2019
DOI: 10.29309/tpmj/2019.26.04.3375
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of Prematurity (Rop);

Abstract: ABSTRACT… Objectives: To find out Association with risk factors of retinopathy of prematurity (ROP) of in-hospital newborns of low birth weight (LBW). Study Design: Cross sectional study. Setting: Department of Paediatrics, Civil Hospital Bahawalpur. Period: March 2017 to May 2018. Material and Methods: Sixty infants having birth weight 800 gram to 2500 gram, gestational age from 28 weeks to 40 weeks, either male or female were selected. Retinopathy of prematurity (ROP) was assessed in selected patients. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
2
3
0
Order By: Relevance
“…A significant relationship between birth weight and ROP was also confirmed by multivariate logistic regression analysis by which birth weight less than 1725 g was associated with a 4.5-fold increase in the risk of ROP (OR = 4.522, 95% CI: 2.677-7.637, P <0.001). This finding is consistent with many previous studies (4,(11)(12)(13)16,17,19).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A significant relationship between birth weight and ROP was also confirmed by multivariate logistic regression analysis by which birth weight less than 1725 g was associated with a 4.5-fold increase in the risk of ROP (OR = 4.522, 95% CI: 2.677-7.637, P <0.001). This finding is consistent with many previous studies (4,(11)(12)(13)16,17,19).…”
Section: Discussionsupporting
confidence: 94%
“…ROP is a multifactorial disease in which low gestational age at birth has been suggested in several studies as an important risk factor for this disease. In studies in India, Pakistan, Mexico, Portugal, Oman, and Isfahan, the gestational age of neonates with retinopathy at birth was significantly lower than that of nonpatients (4,11,13,14,16,17), which are in accordance with our findings. In a study by Ludwig et al (2017) in the United States, multivariate regression analysis showed that gestational age was an independent predictor of ROP (12), which is similar to the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast,Ali et al, [10] found that, male sexual orientation was incorporated among hazard factors for serious, treatment-requiring ROP, birth head perimeter, birth length were fundamentally connected to ROP requiring treatment.…”
Section: Discussionmentioning
confidence: 94%